Phentermine plus topiramate for the treatment of obesity. Issue 5 (September 2012) - Powell, Amanda; Aronne, Louis J; Apovian, Caroline M
A novel combination therapy is currently being investigated for the treatment of obesity. Phentermine plus topiramate has shown efficacy in both Phase II and III trials as compared with either drug used alone. With average 2-year weight loss as high as 10.5% and reduction of up to 76% in the incidence of progression of Type II diabetes, combination phentermine plus topiramate may provide significant benefit in conjunction with behavioral modification in the management of obesity. However, as with any new pharmacologic treatment option, the risk/benefit profile needs to be carefully assessed.